Mitochondrial-ER Contact Sites and Tethers Influence the Biosynthesis and Function of Coenzyme Q - Noelle Alexa Novales; Hadar Meyer; Yeynit Asraf; Maya Schuldiner; Catherine F. Clarke (Contact)
Coenzyme Q (CoQ) is an essential redox-active lipid that plays a major role in the electron transport chain, driving mitochondrial ATP synthesis. In Saccharomyces cerevisiae (yeast), CoQ biosynthesis occurs exclusively in the mitochondrial matrix via a large protein-lipid complex, the CoQ synthome, comprised of CoQ itself, late-stage CoQ-intermediates, and the polypeptides Coq3-Coq9 and Coq11. Coq11 is suggested to act as a negative modulator of CoQ synthome assembly and CoQ synthesis, as its deletion enhances Coq polypeptide content, produces an enlarged CoQ synthome, and restores respiration in mutants lacking the CoQ chaperone polypeptide, Coq10. The CoQ synthome resides in specific niches within the inner mitochondrial membrane, termed CoQ domains, that are often located adjacent to the endoplasmic reticulum-mitochondria encounter structure (ERMES). Loss of ERMES destabilizes the CoQ synthome and renders CoQ biosynthesis less efficient. Here we show that deletion of COQ11 suppresses the respiratory deficient phenotype of select ERMES mutants, results in repair and reorganization of the CoQ synthome, and enhances mitochondrial CoQ domains. Given that ER-mitochondrial contact sites coordinate CoQ biosynthesis, we used a Split-MAM (Mitochondrial Associated Membrane) artificial tether consisting of an ER-mitochondrial contact site reporter, to evaluate the effects of artificial membrane tethers on CoQ biosynthesis in both wild-type and ERMES mutant yeast strains. Overall, this work identifies the deletion of COQ11 as a novel suppressor of phenotypes associated with ERMES deletion mutants and indicates that ER-mitochondria tethers influence CoQ content and turnover, highlighting the role of membrane contact sites in regulating mitochondrial respiratory homeostasis.